Efektivitas Brand Ambassador NCT 127 Pada Produk Skincare Nature Republic di Kalangan Penggemar NCT Di Media Sosial Twitter - Asrul Nur Iman (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
Nature Republic is one company that uses brand ambassadors to attract consumer interest. Nature Republic is also one of the most famous beauty products among beauty enthusiasts. This study determined the effectiveness of using NCT 127 as a brand ambassador for Nature Republic skincare products among fans. This study uses descriptive quantitative methods by distributing the questionnaire to 100 respondents on social media Twitter who are followers of the @nctzenbase account with a Likert scale. The result of this study is that the NCT 127 brand ambassador is proven to be effectively used by Nature Republic by looking at the values in the ViscCAP theory. This study proves that the indicator power is the most effective VisCAP indicator on NCT 127 as a brand ambassador.